Studi Pemisahan Bijih Mangan dari Paludda Daerah Barru Menggunakan Shaking Table dengan Variasi Ukuran Butir: Separation Study of Manganese Ore from Palludda Barru Region Using Shaking Table with Variation of Grain Size Fraction - Bakri, Suriyanto; Ratmi Nurhawaisyah, Sitti; Nurmalasari; Iksan, Muh.; Prayitna, Yusri; Putri, Syukrika (CV Insight Publisher, 2025)
Manganese is one of the mineral products of mining, especially those found in Indonesia, such as in the Paludda area of Barru Regency, South Sulawesi. Manganese ore is known as raw material for steel industry, battery industry and chemical industry. This research was conducted at the Mining Engineering Study Program's Materials Processing Laboratory. The purpose of this study was to determine the percentage increase in manganese ore content after the concentration process, determining the recovery of manganese ore against variations in grain size using a shaking table. The analysis used in this research includes shaking table equipment, XRF analysis and also XRD analysis, from this processing will be obtained Mn content. The results of this study show shaking table separation using operating variables with an initial sample weight of 500 grams with levels in the initial sample of MnO of 33.58%, in concentrate -65 of 26.60%, concentrate -100 of 25.93%, concentrate -150 of 25.46%, concentrate -200 of 26.93%, in tailings -65 of 24.17%, tailings -100 of 23.79%, tailings -150 of 22.79% and tailings -200 of 22.60. Therefore, the results of the study can be concluded that the shaking table operation obtained the optimal concentrate and tailings in the -150 MnO concentrate with a recovery of 23.65%, then the -100 MnO tailings with a recovery of 38.68%